Development of an alternative zebrafish model for drug‐induced intestinal toxicity. Issue 2 (13th October 2017) - Ryu, Bokyeong; Kim, C‐Yoon; Oh, Hanseul; Kim, Ukjin; Kim, Jin; Jung, Cho‐Rok; Lee, Byoung‐Hee; Lee, Seungki; Chang, Seo‐Na; Lee, Ji Min; Chung, Hyung‐Min; Park, Jae‐Hak
Abstract: An evaluation of intestinal toxicity is important because the mucosal lining of the gastrointestinal tract is the first barrier for oral xenobiotics. Until now, a rat model has been recommended as the standard intestinal toxicity model and the Caco‐2 cell line, originated from a human colon adenocarcinoma, has been used as an alternative to this model, but there are limitations regarding cost‐effectiveness and the need for mimicry of the human system. In this study, we investigated whether zebrafish could be a valid alternative to rats and Caco‐2 cells as an intestinal toxicity model. We focused on intestinal gene expression of cytochrome P450 3A65, oxidative stress, apoptosis, inflammation, and intestinal function. Reverse transcription–quantitative polymerase chain reaction analysis was conducted using three models: zebrafish, Sprague–Dawley rats and Caco‐2 cells, and the transcript levels and patterns of indicator genes were analyzed in conjunction with histopathological changes. Our results suggested that representative intestinal toxicants, indomethacin, diclofenac and methotrexate, induced significant transcript level changes in marker genes such as CYP3A, inducible nitric oxide synthase, heme oxygenase 1, superoxide dismutase 1, glutathione peroxidase 1, BCL2 associated X, B‐cell lymphoma 2, caspase 9, tumor protein p53, nuclear factor‐κB, interleukin‐1β, tumor necrosis factor‐alphaα and toll‐like receptor 2 in the zebrafish model as in the rat and Caco‐2 cells models. These results suggest that zebrafish model is sufficiently worth developing as an intestinal toxicity model that can replace or compensate the rat model or Caco‐2 cell model. Abstract : An evaluation of intestinal toxicity is important, but rat models and Caco‐2 cell lines have been proved to have limitations. We investigated zebrafish as an alternative intestinal toxicity model. Transcript levels related to intestinal metabolism, damages, and functions and histopathological changes were analyzed in zebrafish, rats and Caco‐2 cells. Our results suggested indomethacin, diclofenac and methotrexate induced significant changes in the zebrafish as in the rat and Caco‐2 cells, and the zebrafish model is worth developing as an alternative.